2020
DOI: 10.1038/s41598-020-70039-5
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnographic phenotyping of obstructive sleep apnea and its implications in mortality in Korea

Abstract: Conventionally, apnea–hypopnea index (AHI) is used to define and categorize the severity of obstructive sleep apnea. However, routine polysomnography (PSG) includes multiple parameters for assessing the severity of obstructive sleep apnea. The goal of this study is to identify and categorize obstructive sleep apnea phenotypes using unsupervised learning methods from routine PSG data. We identified four clusters from 4,603 patients by using 29 PSG variable and arranged according to their mean AHI. Cluster 1, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 48 publications
0
14
1
Order By: Relevance
“…A similar phenotype to OSA and PLM was found in a Korean study where, similarly to our study, it was the least common and with the highest PLMS count, oldest patient group and lowest Epworth sleepiness scale scores. The main difference to our study, was that these patients had the lowest quality of sleep, which contributes to higher arousal and awakening rates mentioned above [24]. In another recently published study, a phenotype related to periodic limb movements was connected to a two-fold higher cardiovascular or cerebrovascular event risk [25].…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…A similar phenotype to OSA and PLM was found in a Korean study where, similarly to our study, it was the least common and with the highest PLMS count, oldest patient group and lowest Epworth sleepiness scale scores. The main difference to our study, was that these patients had the lowest quality of sleep, which contributes to higher arousal and awakening rates mentioned above [24]. In another recently published study, a phenotype related to periodic limb movements was connected to a two-fold higher cardiovascular or cerebrovascular event risk [25].…”
Section: Discussioncontrasting
confidence: 64%
“…A close to Severe OSA phenotype, which displayed AHI average of almost 70 times/hour, was described in the earlier mentioned Korean study, and was associated with a higher cardiovascular and cerebrovascular event risk [24]. Another study compared different phenotypes between men and women and discovered, that both sexes had phenotypes with severe OSA features [26].…”
Section: Discussionmentioning
confidence: 68%
“…Lastly, the diagnostic method of sleep apnea may not be unified. However, the diagnosis of sleep apnea was usually done using polysomnography according to recently published data in Korea 40 , 41 . Since the aim of this study was not about the exact diagnosis of OSA, but to examine the relationship between clinically significant OSA and NAFLD, we used the ICD-code to define OSA as previous study 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The most notable cluster analysis study done on OSA was the Icelandic Sleep Apnea Cohort (ISAC) that identified three subgroups-disturbed sleep group, minimally symptomatic group, and excessive daytime sleepiness group-using validated sleep-related questionnaires in addition to comorbid conditions [15]. Several other studies from Europe and Asia ensued clustering based on multiple polysomnography (PSG) variables, demographic factors, sleep-related symptoms, comorbidities, and some studies obtained similar results whereas others ended up with different clusters [16][17][18][19].…”
Section: Cimmentioning
confidence: 99%